Driving Backwards Using a Semi-Autonomous Smart Wheelchair System (DSS): A Clinical Evaluation - Vinod Sharma; Richard Simpson; Edmund LoPresti; Mark Schmeler (Applied Bionics and Biomechanics)
Some wheelchair users have difficulty looking backward when backing up in confined spaces due to limited neck range of motion or low vision, which can lead to collisions which may result in personal injury or property damage. The Drive Safe System (DSS) was evaluated in a controlled laboratory setting with blindfolded able-bodied individuals on various backward driving tasks. Performance with the DSS was compared with a standard white cane used for navigation assistance by people with visual impairment. Results indicate that the DSS significantly reduced the number of collisions compared to using a cane (p = 0.0001) alone. There was no difference in task completion time when participants were using the cane or the DSS (p = 0.915). Users rated the DSS favourably as they experience less total workload (p = 0.026), less physical demand (p = 0.006), felt less frustrated (p = 0.002) and put less effort (p = 0.007) to achieve better performance when using the DSS, compared to using a cane. These findings suggest that the DSS can be a viable powered mobility solution for wheelchair users with visual impairments.